Pir Gohar "The Poet of Peace" - Khan, Taj Nabi; Ahmad, Mazhar (sourcecoder, 2024)
The Pashtun land has always been a battlefield, but it is natural that no matter how many attempts have been made to set fire here and no matter how many wars have been fought, as a result, the writers here did not fight as a reaction, but these writers and poets. The image of peace has been prominent in poetry. In this regard, every poet raised the slogan of peace and decorated his poetry with the ornament of peace. In this way, there are poetry related to peace in Pir Gohar's poetry, he also received the award: "Poet of Peace" in this regard.